Pathway to Care of Psychiatric Services in Gandaki Medical College Teaching Hospital in Western Nepal - Lamichhane, N.; Thapa, DK; Timilsina, RR; Sharma, R.; Vaidya, L; Subedi, A (Journal of Gandaki Medical College-Nepal, 2019)
Aims and Objectives: The sequence of contacts with individuals and organizations prompted by the distressed person's efforts, and those of his or her significant others, to seek help is known as the pathways to care. The study of the pathways to care provides the relevant information regarding the individual's health seeking and illness behaviour. A wide range of professionals including psychiatrists, psychologists, other doctors, faith-healers and religious healers cater to the needs of mentally ill patients. This study was carried out to identify the pathway to care of patients up to psychiatric care with no prior psychiatric treatment at GMCTH.Methodology: It is a cross-sectional, descriptive study conducted in GMCTH, Pokhara from Jan 2015 to Dec 2016. After ethical consideration, all new patients and those newly referred to the psychiatric services and agreed to participate were interviewed until the target 100 participants were recruited. ICD-10 was used for diagnosis. Data were computed and analyzed by using Microsoft excel and SPSS. Parametric & non parametric statistical technique was applied wherever appropriate.Results: Total of 100 patients (56 females, 44 males) was included in the study. Mean age of the entire study cohort was 37.17 years (SD 15.45). The mean no. of months to seek first help from a psychiatrist was 53.03 months (SD: 81.70).Conclusion: All the patients here eventually made treatment contact with psychiatrists. However, delay was pervasive. Delay in treatment has negative effect in the treatment outcome. The knowledge and recognition of psychological disorders by the traditional healers as well as other treatment providers in the community are crucial for early treatment of psychiatric patients.